Effectiveness of Antihypertensive Medication on Blood Pressure Reduction among Hypertensive Patients: A Pre-Post Study in Heart Hospital in Nepal - Laudari, Shankar; Dhakal, Abiona; Timilsena, Nabodit; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2025)
Background: Hypertension is a major public health concern and a leading risk factor for cardiovascular diseases. This study was aimed to evaluate the effectiveness of antihypertensive medication in reducing systolic and diastolic blood pressure among adult patients. Methods: A pre-post intervention study was conducted among 50 hypertensive patients (19 females and 31 males). Blood pressure was measured before and after administration of antihypertensive medication/s. Paired sample t-tests were used to compare pre- and post-treatment values, and effect sizes were calculated using Cohen’s d and Hedges’ correction. Results: In the overall population, the mean systolic blood pressure significantly decreased from 182.8 ± 24.99 mmHg to 130.2 ± 15.58 mmHg (mean difference = 52.6 mmHg, p < 0.001), and diastolic pressure from 113 ± 13.13 mmHg to 85.6 ± 9.07 mmHg (mean difference = 27.4 mmHg, p < 0.001), with large effect sizes (Cohen’s d = 2.519 for systolic, 1.941 for diastolic). Similar significant reductions with large effect sizes were observed among both male and female subgroups. Conclusion: Antihypertensive medications were highly effective in significantly lowering both systolic and diastolic blood pressure in the study population. These findings support the continued use of pharmacological intervention as an essential component of hypertension management across both sexes.